1998
DOI: 10.1021/jo980546s
|View full text |Cite
|
Sign up to set email alerts
|

Isophosphoramide Mustard and Its Mechanism of Bisalkylation

Abstract: To investigate the mechanism(s) of bisalkylation by isophosphoramide mustard (IPM), IPM-beta,beta,beta',beta'-d(4) was synthesized and the products of its reaction with thiosulfate (at pD 7.0) were analyzed by NMR. By both (1)H and (13)C NMR, the distribution of deuterium in the products was consistent with bisalkylation through sequential aziridinyl intermediates [(NCH(2)CD(2)S):(NCD(2)CH(2)S) = 53:47]. Under the given reaction conditions, label scrambling as a result of thiosulfate acting as a leaving group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Thus, it was possible to obtain good estimations of IPM-Cl 2 , IPM-Cl/Alk, and IPM-Alk 2 abundances as a function of time, and hence estimations of k exp1 and k exp2 . These rate constants values are in close agreement with those described previously (Springer et al, 1998).…”
Section: P Mnr Kinetic Study Of Mustard Alkylating Activitysupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, it was possible to obtain good estimations of IPM-Cl 2 , IPM-Cl/Alk, and IPM-Alk 2 abundances as a function of time, and hence estimations of k exp1 and k exp2 . These rate constants values are in close agreement with those described previously (Springer et al, 1998).…”
Section: P Mnr Kinetic Study Of Mustard Alkylating Activitysupporting
confidence: 81%
“…This signal has been assigned previously to IPM-Alk/Cl (Fig. 5A) (Springer et al, 1998). It has been shown that in the reaction sequence IPM-Cl 2 3 IPM-Cl/Alk 3 IPM-Alk 2 , the formation of both IPM-Alk/Cl and IPM-Alk 2 was preceded by an intramolecular cyclization of the chloroethylamido functionality, resulting in the formation of an aziridine.…”
Section: P Mnr Kinetic Study Of Mustard Alkylating Activitymentioning
confidence: 93%
“…Phosphoramide mustard is a DNA-reactive alkylating agent that binds to the N 7 position of guanine (6,9). Phosphoramide mustard may also react with the O 6 position of guanine (6) and has been implicated in DNA cross-linking (10). Acrolein is believed to contribute to DNA damage primarily by creating abasic sites and single-strand breaks (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The mechanism of bisalkylation by isophosphoramide mustard was examined using the D 4 -labelled isotopomer and analysing the deuterium distribution in the product using 1 H and 13 C NMR spectroscopy [190] (Fig. 59).…”
Section: Biosynthetic Studiesmentioning
confidence: 99%